Choanoflagellate and choanocyte collar‐flagellar systems and the assumption of homology. Issue 1 (6th January 2014) - Mah, Jasmine L.; Christensen‐Dalsgaard, Karen K.; Leys, Sally P.
SUMMARY The similarities between the choanoflagellates and the choanocytes of sponges have been discussed for more than a century yet few studies allow a direct comparison of the two. We reviewed current knowledge of the collar and flagellum and compared their structure and function in the choanoflagellate Monosiga brevicollis and the sponge Spongilla lacustris. Collar microvilli were of similar length and number, but the shape of the collar differed between the two cells. In Monosiga, collars were flared and microvilli were joined by a single band of glycocalyx mid‐way along their length; in Spongilla, collars formed a tube and microvilli were joined by a mesh of glycocalyx. Monosiga flagella beat at least four times faster than those in Spongilla. Flagellar vanes were found in both cell types. In both cells, the flagella and so probably also the vanes maintained moving points of contact with the microvilli, which suggested that collars and flagella were integrated systems rather than independent units. There were fundamental differences in how the collar and flagella interacted, however. In Spongilla, the flagellum bent upon contact with the collar; the flagellar amplitude was fitted to the collar diameter. In Monosiga, the flagellar amplitude was unaffected by the collar; instead the collar diameter appeared fitted to the flagellum. These differences suggest that though choanocytes and choanoflagellates are similar, homology cannot be taken for granted. Similarities in collar‐flagellum systems separated by 600 million years of evolution, whether maintained or convergent, suggest that these form important adaptations for optimizing fluid flow through micro‐scale filters.